Clinical-imaging and therapeutic evaluation of nodule-mass pulmonary cryptococcosis and pneumonia-type pulmonary cryptococcosis - Yanli Zhang; Ling Liu; Wei Li; Chao Ran (BMC Pulmonary Medicine)
Abstract Background The different morphological changes of pulmonary cryptococcosis (PC) cause difficulties in diagnosis and treatment. To evaluate the clinical-imaging and therapeutic differences between nodule-mass PC and pneumonia-type PC. Materials and methods The clinical-imaging data of 68 patients with PC were collected, including nodule-mass PC (36 cases) and pneumonia-type PC (32 cases). Their clinical-imaging findings were retrospectively analyzed to determine the independent discriminators. Their diagnostic and therapeutic effects were compared. Results Compared with nodule-mass PC, pneumonia-type PC was more common with respiratory symptoms (19.4% vs. 81.3%, P < 0.001), inflammatory response (16.7% vs. 71.9%, P < 0.001), bilateral distribution (16.7% vs. 68.8%, P < 0.001), mediastinal lymphadenopathy (0 vs. 21.9%, P = 0.010) and pleural effusion (0 vs. 25%, P = 0.005). While CT malignant signs were more common in nodule-mass PC (66.7% vs. 12.5%, P < 0.001). Multivariate logistic regression analysis showed respiratory symptoms, inflammatory response, bilateral distribution, and malignant CT signs were independent discriminators, with moderate areas under the curve (AUC, 0.760–0.809). Their combined efficacy was significantly improved, with the highest AUC (0.937). Unlike pneumonia-type PC, nodule-mass PC was often treated with low-dose, short-term monofluconazole treatment. However, both groups showed good therapeutic effects. Conclusion Respiratory symptoms, inflammatory response, bilateral distribution, and malignant CT signs were different between nodule-mass PC and pneumonia-type pulmonary PC. Combining these independent discriminators could reveal its clinical-imaging diversity. The graded antifungal therapy based on CT morphology was effective.